HUBUNGAN ANTARA SIKAP TERHADAP PENELITIAN DAN HAMBATAN PENELITIAN DENGAN KETERLIBATAN DALAM PENELITIAN MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MATARAM - Puspitasari, Susi; Susani, Yoga Pamungkas; Maulana, Akhada (Faculty of Medicine Universitas Mataram, 2021)
Background: conducting research is beneficial for the future of a medical doctor, but the medical students in Mataram University have unsatisfactory results in the course of research methodology. Research is also a determinant of the quality of a university. In a medical study, students are required to review or conducting relevant research as the proponent of their professionalism as long life learner. Regarding this study, it aims to measure the relationship of attitude and barriers towards research experiences of students in the medical faculty of Mataram University. Method: this study belonged to a quantitative study with a cross-sectional survey design. The subjects in this study were 129 medical students from a total of 140 of medical students in Mataram University in their 3-year and 4-year study. They have taken a research methodology course as the prerequisite to fill Revised Attitude Towards Research (R-ATR) questionnaire to measure attitude toward research, the questionnaire for both barriers and research experiences. Data from this study were analyzed using Spearman correlation. Results: Attitude toward research and research experience have small and positive correlation (r=0,322;p <0,001), while research barrier is small and negatively correlated towards research experience (r=-0,209;p <0,05). Conclusion: attitudes and barriers can be the factors that affected the frequency of student’s experiences in research.